Injury-related mortality in South Africa: a retrospective descriptive study of postmortem investigations - Richard Matzopoulos; Megan Prinsloo; Victoria Pillay-van Wyk; Nomonde Gwebushe; Shanaaz Mathews; Lorna J Martin; Ria Laubscher; Naeemah Abrahams; William Msemburi; Carl Lombard; Debbie Bradshaw (The World Health Organization, 2015)
Abstract Objective To investigate injury-related mortality in South Africa using a nationally representative sample and compare the results with previous estimates. Methods We conducted a retrospective descriptive study of medico-legal postmortem investigation data from mortuaries using a multistage random sample, stratified by urban and non-urban areas and mortuary size. We calculated age-specific and age-standardized mortality rates for external causes of death. Findings Postmortem reports revealed 52 493 injury-related deaths in 2009 (95% confidence interval, CI: 46 930-58 057). Almost half (25 499) were intentionally inflicted. Age-standardized mortality rates per 100 000 population were as follows: all injuries: 109.0 (95% CI: 97.1-121.0); homicide 38.4 (95% CI: 33.8-43.0; suicide 13.4 (95% CI: 11.6-15.2) and road-traffic injury 36.1 (95% CI: 30.9-41.3). Using postmortem reports, we found more than three times as many deaths from homicide and road-traffic injury than had been recorded by vital registration for this period. The homicide rate was similar to the estimate for South Africa from a global analysis, but road-traffic and suicide rates were almost fourfold higher. Conclusion This is the first nationally representative sample of injury-related mortality in South Africa. It provides more accurate estimates and cause-specific profiles that are not available from other sources.